PENGARUH TAX PLANNING TERHADAP RETURN SAHAM YANG DIMODERASI OLEH KONSERVATISMA AKUNTANSI DENGAN VARIABEL KONTROL UKURAN PERUSAHAAN - Wisnu Haryo Pramudya (Akademi Akuntansi YKPN Yogyakarta, 2016)
The purpose of this study was to examine the effect of tax planning on stock returns and test the accounting conservatism as a firm's control structur to moderating influence tax planning on stock returns. In this study, the independent variable is the tax planning and the dependent variable is stock returns. The moderation variable accounting conservatism with variable control the size of the company. This study uses MRA (Moderated Regression Analysis). MRA is a form of regression which is designed essentially to define the relationship between two variables that are influenced by a third variable/moderator, the regression equation contains elements or multiplicative interaction between two or more independent variables. The study population was all real estate companies and contractors listed on the Indonesia Stock Exchange ( BEI ) from 2008-2012. The sampling method used is the purposive sampling. Before performing regression analysis, has performed classical assumption and all the assumptions of classical test is met, then the results of the regression analysis as follows: (1) The results of regression analysis showed that the effect of tax planning on stock returns and the effect is a positive influence. (2) The test results provide empirical evidence that the interaction between accounting conservatism applied by the company with the Tax Planning positive and significant impact on stock returns. From the results of the regression analysis it can be concluded that the first hypothesis (H1) and the second hypothesis (H2) in accordance with the formulation of acceptable statistical researchers. Key Word: tax planning, return saham dan konservatisma akuntansi